2022
DOI: 10.3390/jcm11195598
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing and Transcriptome Profiling in Twins Discordant for Mayer-Rokitansky-Küster-Hauser Syndrome

Abstract: To identify potential genetic causes for Mayer-Rokitansky-Küster-Hauser syndrome (MRKH), we analyzed blood and rudimentary uterine tissue of 5 MRKH discordant monozygotic twin pairs. Assuming that a variant solely identified in the affected twin or affected tissue could cause the phenotype, we identified a mosaic variant in ACTR3B with high allele frequency in the affected tissue, low allele frequency in the blood of the affected twin, and almost absent in blood of the unaffected twin. Focusing on MRKH candida… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Variants were then manually re‐annotated using diagnostic criteria of the ACMG 17 . Only individuals with pathogenic or likely pathogenic variants were included, which were present in 23 articles 1,2,4–6,8–12,18–30 . We also characterized the ascertainment criteria with which these studies identified individuals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Variants were then manually re‐annotated using diagnostic criteria of the ACMG 17 . Only individuals with pathogenic or likely pathogenic variants were included, which were present in 23 articles 1,2,4–6,8–12,18–30 . We also characterized the ascertainment criteria with which these studies identified individuals.…”
Section: Methodsmentioning
confidence: 99%
“…17 Only individuals with pathogenic or likely pathogenic variants were included, which were present in 23 articles. 1,2,[4][5][6][8][9][10][11][12][18][19][20][21][22][23][24][25][26][27][28][29][30] We also characterized the ascertainment criteria with which these studies identified individuals.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also reported carrying variants in both TBX6 and LHX1 or a CNV in combination with TBX6 variants might play a role in the etiology of Mullerian aplasia (Sandbacka et al, 2013). Interestingly, since only some of the cases have been attributed to genetic anomalies, other presumption of pathologic mechanisms such as epigenetics and somatic mutations have been suggested to play a role in Mullerian aplasia (Buchert et al, 2022; Hentrich et al, 2020). And the application of techniques including whole genome sequencing (WGS) and RNA‐seq is expected to provide new clues hopefully (Buchert et al, 2022; Hentrich et al, 2020; Pan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%